A Dynamic Model of Membrane Recovery Mechanisms in Bacteria following High Pressure Processing. Issue 1 (2019) - Nikparvar, B.; Subires, A.; Capellas, M.; Hernandez, M.; Bar, N.
Abstract: High pressure processing (HPP) in the food industry is considered as an alternative to conventional thermal treatments for inactivation of pathogenic bacteria. However, a major concern in this field is the ability of some pathogens such as Listeria monocytogenes to recover pressure-induced damages after HPP even during cold temperature storage. Based on our observation using electron microscopy and flow cytometry techniques, membrane of Listeria monocytogenes is one of the main structures in this microorganism which is damaged by pressurization. We quantify this damage by estimating the radius of holes created on the membrane after pressure exposure of 400 [MPa] lasting for 8 and 20 [min]. The flow cytometry result with two fluorescent molecules at different time points after pressurization supports the existence of a recovery process. We propose a novel model consisting of six ordinary differential equations, wired by a feedback regulatory network to investigate the dynamics of hole recovery after HPP. The model is developed based on a hypothesized repair mechanism, similar to the well-established pathways that bacteria activate in response to general types of stress. Simulation results show a nonlinear behaviour of the hole recovery and fitted to the experimental points very well. The maximum estimated hole radius is approximately 0.9 [nm] and 0.7 [nm] for 400 [MPa], 8 [min] and 400 [MPa], 20 [min], respectively. The model provides a valuable tool to estimate the membrane damage and recovery in live bacteria following HPP.